Assessment of environmental impact, energetics and productivity of small-farm integrated farming system model under irrigated situation of semi-arid ecosystem of India - SAMMAURIA, R; SINGH, HARPHOOL; YADAV, M R; SINGH, PRATIBHA; MEENA, O P; GUPTA, K C; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2025)
Small and marginal farmers in semi-arid regions often practice crop-dominated farming systems, which tend to have low productivity and negative environmental impacts. Transforming these farms into Integrated Farming Systems (IFS) could address multiple challenges. The current study was carried out during 2020–21 to 2021–22 at All India Coordinated Research Project on IFS, Rajasthan Agricultural Research Institute, Durgapura, Rajasthan, to estimate the greenhouse gas (GHG) emission, energy and carbon budgeting of crop-livestock-horticulture based IFS model of 1.45 ha. This IFS model produced mean annual Pearl Millet Equivalent Yield (PEY) of 37,209 kg/year. Among the enterprises, dairy contributed the highest (35.84%) in the mean annual production followed by crops (24.37%). Likewise, the mean annual net return of the IFS model was ₹3,31,853, wherein dairy component contributing the highest (33.09%) followed by crops (29.60%) along with mean annual employment of around 779 man-days. This model consumed 263808 MJ of energy input annually against the total output of 321866 MJ. The model was energy efficient with the mean energy use efficiency of 1.22 and net energy gain of 58058 MJ. This model sequestrated nearly 7324.4 kg CO2–e as sink through tree components (4978 kg CO2–e) and incorporated manures or crop residues (2346.4 kg CO2–e). The results indicated that with diversified cropping (cereals, pulses, oilseed), livestock (dairy, goat, poultry), horticulture (vegetable and mixed orchard) based current IFS model may be a climate smart option for small farmers in the study area to enhance the productivity, profitability, energy use and carbon sequestration to minimize the environmental impact.